Analysis into the partitioning of a quaternary ammonium salt between oil and water phases (International Journal of Biology and Chemistry, 2020)
Partitioning of corrosion inhibitors between oil/water phases is one of main factors governing the inhibitor performance. It is important for the inhibitor to be dissolved in water phase at a particular concentration in order to provide protection from corrosion. Partitioning behaviour of a quaternary ammonium salt that is widely used as a corrosion inhibitor was studied by carrying out partitioning tests and determining the concentration of the inhibitors by conventional colorimentry method. The tests were performed using various water cuts, hydrocarbon phases, and concentrations in order to find out the effects of these factors. Comparison of partitioning behaviour of the inhibitors in low and high water cut mixtures resulted in some loss of the inhibitor from bulk water phase as water cut decreased. Partitioning of quaternary ammonium compound seems to be dependent on the nature of the hydrocarbon phase. Also, general suggestions about silanisation procedure of glassware were made.